Generalized Gribov-Lipatov Reciprocity and AdS/CFT - Matteo Beccaria; Valentina Forini; Guido Macorini (Advances in High Energy Physics)
Planar 𝒩=4 SYM theory and QCD share the gluon sector, suggesting the investigation of Gribov-Lipatov reciprocity in the supersymmetric theory. Since the AdS/CFT correspondence links 𝒩=4 SYM and superstring dynamics on Ad S 5